Family Investment Strategies in Pre-modern Societies: Human Capital, Migration, and Birth Order in Seventeenth and Eighteenth Century England - Marc Klemp; Chris Minns; Patrick Wallis; Jacob Weisdorf (European Historical Economics Society (EHES), 2012)
This paper uses linked apprenticeship-family reconstitution records to explore the influence of family structure on human capital formation in preindustrial England. We observe a small but significant relationship between birth order,resources and human capital investments. Eldest sons were less likely to be apprenticed, particularly among farming families. Mortality shocks in the household led to significant delay in the timing of apprenticeship. We also find that many apprentices maintained contact with their home parish, returning to wed and establish a new household. The "middling sorts" that dominated apprenticeship behaved more like modern families than the pre-industrial elite.
Keywords: 330